HEGEMONY OF DUTCH COLONIAL GOVERNMENT AGAINST THE EXISTENCE OF MINANGKABAU ANCIENT MANUSCRIPTS WITH ARABIC-MALAY - Yona Primadesi (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2015)
HEGEMONI PEMERINTAH KOLONIAL BELANDA TERHADAP KEBERADAAN NASKAH-NASKAH KUNO MINANGKABAU BERAKSARA ARAB-MELAYUAbstractFar before the Netherland colonial came to Indonesia, Indonesian people is a very eductead people. Proves with the development of traditional education that use local font in the whole country, on of them is Minangkabau. Local font of Minangkabau is the adaptation of Arabian font along with the culture of the people there that is brought by the Arabia merchants, and well known with Arab-Melayu font or Arab without marker. Arab-Melayu font is thaught in the traditional Minangkabau education system through mosque. Besides, Arab-Melayu fontis the background of toward the existence of some texts which contains the value of life of Miangkabau people at that time. However, the existence of Arab-Melayu font try to move, especially when the Netherland colonial try to authorize by introducing latin font to Minangkabau people. The hegemony of latin font cause the degradation of Arab-Melayu font, that implicates to the dissapear of some texts like some scripts or memory that is saved in the old Minangkabau people’s mind. Other than that, the hegemony of politics that is offered by The Netherland’s government caused many Minangkabau scripts become not appropriate to be published and also most of the scripts is voluntary given to the Netherland’s government or as a gift. Key Words: Minangkabau scripts, The Netherland’s colonial, hegemony, local fontAbstrakJauh sebelum penjajah Belanda datang ke Indonesia, orang Indonesia adalah orang yang sangat edukatif. Terbukti dengan berkembangnya pendidikan tradisional yang menggunakan aksara lokal di seluruh negeri, di antaranya adalah Minangkabau. Aksara lokal Minangkabau adalah adaptasi dari aksara Arab bersama dengan budaya orang-orang di sana yang dibawa oleh para pedagang Arabia, dan terkenal dengan aksara Arab-Melayu atau Arab gundul. Aksara Arab-Melayu masuk dalam sistem pendidikan tradisional Minangkabau melalui masjid. Selain itu, aksara Arab-Melayu merupakan latar belakang adanya beberapa teks yang berisi nilai kehidupan orang-orang Minangkabau saat itu. Namun, keberadaan aksara Arab-Melayu mencoba terdesak, terutama saat penjajah Belanda mengenalkan aksara latin kepada masyarakat Minangkabau. Hegemoni aksara latin menyebabkan degradasi aksara Arab-Melayu, yang berimplikasi pada menghilangnya beberapa teks seperti beberapa skrip atau memori yang tersimpan dalam pikiran orang Minangkabau tua. Selain itu, hegemoni politik yang ditawarkan oleh pemerintah Belanda menyebabkan banyak naskah Minangkabau tidak sesuai untuk diterbitkan dan juga sebagian besar skripnya secara sukarela diberikan kepada pemerintah Belanda atau sebagai hadiah.Kata kunci: Skrip Minangkabau, hegemoni kolonial Belanda, aksara lokal